Serum Estradiol Level as a Predictor of Ovarian Response and Pregnancy Outcome During Controlled Ovarian Hyperstimulation in Women from Gaza Strip - Yassin, Maged M.; Laqqan, Mohammed M.; Alzmaily, Eman S. (Journal of Medicine, 2013)
Background: Currently, controlled ovarian hyperstimulation (COH) is monitored by serum estradiol (E2) levels which are believed to primarily detect functional activity of follicles. Objective: To evaluate estradiol level as a predictor of ovarian response and pregnancy outcome during COH in women from Gaza Strip. Methods: This prospective cohort study consisted of 75 women attending in vitro fertilization (IVF) at Al-Basma Fertility Center in Gaza City. Blood withdrawal for E2 hormone measurement was performed in all the patients and the number of oocytes and embryos were recorded for each female and the occurrence of pregnancy was followed for three months. Obtained data were computer analyzed using SPSS statistical package version 18. Results: The mean age of the study population was 29.2±5.9 years. Questionnaire interview showed that the cause of infertility was mostly referred to husbands. More than half of women seeking IVF had no children and had repeated IVF. The mean level of E2 showed the highest value of 2194.4 (pg/ml) at age group 26-35 years. However, the difference in E2 levels among the age groups was not significant (F=0.940 and P=0.395). When related to the number of oocytes retrieved, E2 level showed general increase with increase ovarian response, recording values of 1642.7, 1665.1, 2156.8 and 1798.7 pg/ml with <4, 4-8, 9-16 and >16 oocytes, respectively, but this change was not significant (F=0.219 and P=0.883). The mean level of E2 showed its maximum value of 2143.6 pg/ml in positive pregnancy. However the difference in E2 levels among the different categories of IVF outcome was not significant (F=0.423 and P=0.656). The numbers of total and mature oocytes, and embryo were significantly increased with increased levels of E2, showing a good response at E2 level=1000-2000 pg/ml. The number of mature oocytes showed positive correlations with E2 and number of embryo (r= 0.159, P= 0.177 and r= 0.890, P=0.000, respectively) and negative correlation with age (r=-0.276, P=.017). Conclusion: Estradiol level 1000-2000 pg/ml at mean age of 27.8±4.9 years, could be a predictor of ovarian response and pregnancy outcome during COH. Consequently, for women to undergo a more likely successful IFV program, it is recommended to optimize E2 level at 1000-2000 pg/ml. DOI: http://dx.doi.org/10.3329/jom.v14i1.14537 J MEDICINE 2013; 14 : 52-56